2021
DOI: 10.3390/ijerph182111542
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Chinese Postgraduate Students’ Mental Health

Abstract: To understand the mental health status of Chinese postgraduate students during the COVID-19 pandemic, we used three online questionnaires: self-rating anxiety (SAS) scale, self-rating depression (SDS) scale, and social avoidance and distress (SAD) scale. A total of 3137 postgraduate students from different regions of China participated in our study. We explored the relationship between participant characteristics and mental health using an analysis of variance (ANOVA). We found that the proportions of responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
2
19
1
Order By: Relevance
“…Medical postgraduates who experienced the COVID-19 outbreak and returned to school life for the first time were in a relatively negative mood, feeling anxious and depressed. Similar to studies reporting the psychological situation of medical students worldwide (35,36), our study also showed that selfrated anxiety and depression were high. Female students were significantly more influenced than male students, and they had lower social support.…”
Section: Discussionsupporting
confidence: 89%
“…Medical postgraduates who experienced the COVID-19 outbreak and returned to school life for the first time were in a relatively negative mood, feeling anxious and depressed. Similar to studies reporting the psychological situation of medical students worldwide (35,36), our study also showed that selfrated anxiety and depression were high. Female students were significantly more influenced than male students, and they had lower social support.…”
Section: Discussionsupporting
confidence: 89%
“…This indicates the worsening mental health condition of this particular population in recent years, especially in the context of the repeated resurgences of the COVID-19 pandemic, which increased the stress of college students and exposed them to new frustrating stressors that caused various mental health concerns [ 2 ]. Given college students’ high stress and anxiety levels during the COVID-19 pandemic [ 88 ], 35 (71%) of the 49 studies [ 2 , 12 , 48 , 49 , 52 - 58 , 61 - 64 , 67 - 69 , 72 - 77 , 81 - 89 , 91 , 92 ] investigated the COVID-19–induced mental health concerns of Chinese undergraduate students and proposed specific interventions in response to the severity of the psychological impact of COVID-19 [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…The interventions proposed in the included studies can be divided into two broad categories: social support and coping strategies. Social support was provided by government authorities [ 49 , 52 - 54 , 61 , 62 , 68 , 72 , 84 , 86 - 88 ]; university authorities [ 12 , 48 , 50 , 51 , 53 - 55 , 57 - 59 , 62 , 64 , 65 , 67 , 69 , 91 , 93 ]; students’ affairs counselors and teachers [ 54 , 75 , 83 - 85 , 87 , 93 ]; family members [ 52 , 54 , 57 , 83 , 94 ]; health care authorities and professionals [ 52 , 63 , 66 , 75 , 77 - 79 , 87 ]; researchers [ 70 , 85 ]; and media-, internet-, and smartphone-based interventions [ 26 , 53 , 55 , 56 , 60 , 71 , 73 , 75 , 77 , 80 , 81 ]. Positive coping strategies were adopted by undergraduate students themselves [ 52 , 82 , 83 , 85 , 86 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perz et al's (2020) validation of the fear of COVID-19 found high anxiety for students of Asian backgrounds. Liang et al (2021) identified Chinese postgraduate students had negative experiences of anxiety and depression, which impacted their mental health and academic work. Participants' responses also showed international students, including Asians and Africans, were quite insecure on campus, at shopping centres and within the larger community.…”
Section: Fear and Insecuritymentioning
confidence: 99%